Pengaruh Kualitas Produk, Persepsi Harga, Dan Citra Merek Terhadap Minat Beli Ulang Laptop Acer Di Kota Bandung - Muhammad Hanif Muhsinin; Esi Fitriani Komara (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research is motivated by the results of the Kurious survey from the Katadata Insight Center (KIC), Acer is the second most popular laptop in Indonesia, which is 79.2% of the total respondents. Based on the top brand award in 2022, Acer laptops are ranked first in the notebook or laptop category with a score of 27.1%. However, in 2023 there was a significant decrease in the Acer brand laptop, which was 5.90% compared to 2022. This indicates a decrease in repurchase interest in Acer brand laptops. This study aims to analyze the effect of product quality, price perception, and brand image on repurchase interest in Acer laptops in Bandung City. The data collection technique used is nonprobability sampling with convenience sampling research with a total of 120 respondents of Acer laptop users who live in Bandung City with an age range of 17 years and over. The data analysis technique used is multiple regression test using SPSS version 26. The results showed that product quality has a positive and significant effect on repurchase interest. Price perception has a positive and significant effect on repurchase intention. Brand image has a positive and significant effect on repurchase intention. Then, product quality, price perception, and brand image simultaneously affect repurchase intention.